Comunicazioni dell'Istituto Papirologico «G. Vitelli» - 12 - Bastianini, Guido; Russo, Simona (Edizioni dell'Istituto Papirologico «G. Vitelli», 2015)
This volume of Comunicazioni dell'Istituto Papirologico «G. Vitelli» is the twelfth of the series since 1995, and is divided into three sections: 1. Editions and rieditions of texts; 2. Critical notes; 3. Chronique de Lexicographie Papyrologique de la vie matérielle. The texts of the first section belong mostly to the collection of the «Vitelli» Institute, but there are also two documents from the Egyptian Museum in Cairo and a fragment from the State Archive of Florence. The four contributions of the second section deal with topics of literary papyrology (exegesis to the classics) and documentary (reading revisions and linguistic notes). The third section, an absolute novelty, introduces the first results of an international research project concerning the lexicon of material culture documented in the papyri from the Hellenistic to the Arab era.